2017
DOI: 10.1007/s41315-017-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of a miniature free-swimming robotic fish based on multi-material 3D printing

Abstract: Research in animal behavior is increasingly benefiting from the field of robotics, whereby robots are being continuously integrated in a number of hypothesis-driven studies. A variety of robotic fish have been designed after the morphophysiology of live fish to study social behavior. Of the current design factors limiting the mimicry of live fish, size is a critical drawback, with available robotic fish generally exceeding the size of popular fish species for laboratory experiments. Here, we present the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…As expected, fluid motion is almost completely along the IPMC axis, causing a momentum exchange, that is responsible for thrust production. Fluid motion is restricted to a rather confined region in the vicinity of the tip of the IPMC, as observed in Chae et al [25] and Phamduy et al [19]. A flow jet is revealed from the tip of IPMC body, where coherent fluid structures are shedding into the wake flow.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…As expected, fluid motion is almost completely along the IPMC axis, causing a momentum exchange, that is responsible for thrust production. Fluid motion is restricted to a rather confined region in the vicinity of the tip of the IPMC, as observed in Chae et al [25] and Phamduy et al [19]. A flow jet is revealed from the tip of IPMC body, where coherent fluid structures are shedding into the wake flow.…”
Section: Resultsmentioning
confidence: 71%
“…Since the flow induced by the IPMC under water motion is restricted towards its tip vicinity, cf. [18,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phamduy et al designed a miniature robotic fish prototype to investigate animal-robot interaction studies. They used 3D-printing technology to manufacture the robot prototype [26]. Afolayan et al proposed a fish-like underwater robot with a body in a thin plastic film manufactured by using a vacuum packaging machine.…”
Section: Introductionmentioning
confidence: 99%
“…A lamprey-based undulatory vehicle (Wilbur et al 2002), a free-swimming robotic batoid ray based on IPMC actuators (Chen et al 2011), and a miniature fish-like robotic swimmer induced by propulsion generated by tail vibrations (Aureli et al 2010) were presented. More recently, a swimming robotic fish was demonstrated that was developed with electromagnetic actuation system and 3D printing (Phamduy et al 2017).…”
Section: Introductionmentioning
confidence: 99%